33 Practice based on the full-time visitation model for pharmaceutical education in the Rizhao region, China. (19th December 2016) - Yang, Hui; Yu, Fengju; Wang, Enqin; Li, Haoyue
Abstract : Objectives: Pharmacists are in demand both because of their knowledge of medical therapy and also due to their skills in basic physical assessment as medical personnel. The traditional 'two stage' teaching approach for pharmaceutical education in China (theoretical teaching in the early stage and practice teaching in the later stage) has some drawbacks, for instance practice time is too concentrated and there is a large gap between students' theory and practice. The aim of this study was to improve the quality of the teaching of pharmacy students. Methods: We use the full-time visitation model in our teaching hospital for pharmaceutical education. A total of 98 pharmacy undergraduates taught using the traditional model and 176 pharmacy students taught using the full-time visitation model were studied from 2013 to 2015 so that an evaluation appraisal system could be designed. The outline of the method to confirm basic vital signs with simulators was first explained and then demonstrated. Simulations reproduced the effects of drugs on the patient's condition, and the students' knowledge and skill in advanced objective structured clinical examination through practical examinations was checked. Results: Pharmaceutical education was conducted using patient simulators for bedside training, seminars in our hospital pharmacies, and physical assessment practice. Using the full-time visitation model, the excellent results of pharmacy students in basic medical knowledge (80.6%), doctor-patient communication (78.02%), clinical ability and skills (70.41%) and other aspects of comprehensive evaluation (81.6%) were better than those of students taught using the traditional model (p < 0.05). However, basic theory was taught better using the traditional model (85.2%) than with the objective structured clinical examination (OSCE) model (79.6%). The results of case study exercises in which students perform physical assessments and collect basic information on patient background were excellent. Conclusions: The full-time visitation model can improve the clinical practical skills of pharmacy students and pharmaceutical education using simulation provides pharmacy students and pharmacists with experience in the different types of medical treatment provided by various healthcare professionals, leading to exploration of new roles for pharmacists in team medical care. Acknowledgments: This research was financially supported by the Project of Application Technology Research and Development Project Foundation in Rizhao (Grant No. 2014SZSH02).